A link between bilirubin levels and atrial fibrillation recurrence after catheter ablation. Issue 3 (March 2019) - Chen, Su-Chan; Chung, Fa-Po; Chao, Tze-Fan; Hu, Yu-Feng; Lin, Yenn-Jiang; Chang, Shih-Lin; Lo, Li-Wei; Tuan, Ta-Chuan; Te, Abigail Louise D.; Yamada, Shinya; Prabhu, Atul; Chang, Ting-Yung; et al.
Abstract : Background: Bilirubin is associated with different cardiovascular diseases. The relationship between bilirubin and atrial fibrillation (AF) remains unclear. The aim of this study is to determine the association between bilirubin and AF recurrence after catheter ablation. Methods: A total of 212 patients who received AF ablation were retrospectively studied. The total bilirubin level, clinical characteristics, and echocardiographic findings were analyzed to predict the outcome of AF ablations. Results: During a mean follow-up period of 12.2 ± 5.8 months, 61 (28.8%) patients had AF recurrence after catheter ablation. The patients with AF recurrence had a larger left atrial (LA) diameter (39.8 ± 6.3 versus 36.7 ± 5.8 mm; p = 0.001) and higher total bilirubin levels (0.82 ± 0.37 versus 0.63 ± 0.29 mg/dL; p < 0.001) than those without recurrence. The patients with recurrence had higher direct and indirect bilirubin levels than patients without recurrence. The total bilirubin level remained an independent predictor of AF recurrence after multivariate analysis (odds ratio, 4.95; 95% CI, 1.65-14.83; p = 0.004). We identified a cut point of the total bilirubin level for predicting AF recurrence by receiver operator characteristic curve (cut point, 0.7 mg/dL; area under the curve, 0.65; p < 0.001). The total bilirubin levels were positively correlated with the neutrophil counts. However, there were no associations among the total bilirubin level, left atrial (LA) diameter, and voltage. Conclusion: Higher serum bilirubin levels were associated with AF recurrence in paroxysmal AF patients following catheter ablation.